ORGANIZATIONAL PROJECTION IN THE EDUCATIONAL FIELD IN THE CONTEXT OF EDUCATIONAL CHANGE MANAGEMENT: THEORETICAL ANALYSIS - Semenets-Orlova I.A. (Pressing Problems of Public Administration, 2015)
The article is dedicated to conceptualization of the organizational projection as a method ofan activity related to educational change management. The author has detected peculiarities ofstaged building an organizational project. The article determined the functional load andopportunities of application of the organizational projection within a system of educational changepublic administration.